FAKTOR YANG BERHUBUNGAN DENGAN GEJALA NEUROTOKSIK AKIBAT PAPARAN PESTISIDA PADA PETANI SAYURAN, DESA SUGIHARJO, KECAMATAN BATANG KUIS, KABUPATEN DELI SERDANG - Dian Maya Sari Siregar; Nurfadilah Nurfadilah (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Problems: Pesticides are the main choice for controlling pests, diseases and weeds. The use of pesticides is widespread throughout the world. Pesticides used by farmers if not used correctly will have a negative impact on farmers' health. Based on the preliminary survey, 5 out of 10 vegetable farmers showed neurotoxic symptoms. The Aim Of The Research: This research aims to determine the factors associated with neurotoxic symptomps on vegetable farmers in Sugiharjo Village, Batang Kuis District, Deli Serdang Regency. Research Method: This study used an observational quantitative design with a cross sectional approach. The population in this study were all vegetable farmers in the research location were all 37 people. Because the total population is only 37 people, all of them are used as samples (total sampling). The tools for data collection are questionnaires (to measure the variables of working period, age, and neurotoxic symptoms) and observation sheets (to measure the variables of PPE use and pesticide type). Data analysis was univariate and bivariate analysis (using chi-square test) through SPSS version 17.0 program. The Results: The chi-square test show the p-value of each variable is PPE usage = 0.002, pesticide type = 0.127, working period = 0.028 and age = 0.001. Conclusions: There is a relationship between the use of PPE, working period, and age with neurotoxic symptoms due to pesticide exposure while pesticide type is not associated with neurotoxic symptoms due to pesticide exposure. Keywords: Neurotoxic, Pesticides, Vegetable Farmers